Decay law and swirl length of swirling gas-liquid flow in a vertical pipe. (April 2021) - Liu, Li; Zhang, Jiarong; Liu, Shuai; Wang, Ke; Gu, Hanyang
Highlights: Flow patterns of decaying swirling gas-liquid flow are identified. Void fraction of swirling flow patterns is measured. Swirl length of swirling flow patterns is reported. Pattern-based decay model for swirl length prediction is proposed. Abstract: Decaying swirling flow is widely utilized in multiphase flow devices for separation, stabilization and heat transfer enhancement. In this paper, based on the image processing technique, the decay law and swirl length of swirling gas-liquid flow induced by a vane-type swirler in a vertical pipe is experimentally and theoretically studied. According to the visual observation, four swirling flow patterns including chain, swirling gas-column, swirling intermittent and swirling annular flow are recognized at the swirler outlet. Due to swirl decay, the chain, swirling intermittent and swirling annular flow revert to inlet non-swirling flows downstream of the swirler, whereas the swirling gas-column flow transforms to slug flow rather than inlet bubble flow. The swirl length of swirling gas-column and swirling intermittent flow increases with liquid superficial velocity increasing or gas superficial velocity decreasing. By contrast, the swirling annular flow exhibits a reverse trend. Based on the theory of angular momentum and the parameter of two-phase swirl number, comprehensive decay models are proposed to predict the swirl length of various swirling flow patterns. The prediction is correlated reasonably well with the experimental data within ±25% deviation in varied flow conditions.